Asymptomatic Congenital Hyperinsulinism due to a Glucokinase-Activating Mutation, Treated as Adrenal Insufficiency for Twelve Years. (9th January 2017) - Morishita, Kae; Kyo, Chika; Yonemoto, Takako; Kosugi, Rieko; Ogawa, Tatsuo; Inoue, Tatsuhide
Abstract : Congenital hyperinsulinism (CHI) caused by a glucokinase- (GCK-) activating mutation shows autosomal dominant inheritance, and its severity ranges from mild to severe. A 43-year-old female with asymptomatic hypoglycemia (47 mg/dL) was diagnosed as partial adrenal insufficiency and the administration of hydrocortisone (10 mg/day) was initiated. Twelve years later, her 8-month-old grandchild was diagnosed with CHI. Heterozygosity of exon 6 c.590T>C (p.M197T) was identified in a gene analysis of GCK, which was also detected in her son and herself. The identification of GCK-activating mutations in hyperinsulinemic hypoglycemia patients may be useful for a deeper understanding of the pathophysiology involved and preventing unnecessary glucocorticoid therapy.